Determinants of the recreational orientation of the Algerian family in light of contemporary social changes - Eddine, Bennoui Nour; Houria, Sadou (The International tax journal, 2026)
This article aims to analyze the determinants of the recreational orientation of the Algerian family in light of contemporary social changes, through a sociological approach that highlights the interaction of economic, cultural, demographic, and technological factors in shaping family leisure patterns. The article is based on the fundamental assumption that family leisure is no longer a secondary activity but a social practice that reflects the structural transformations affecting the Algerian family within the context of urbanization, globalization, and digitalization. The study found that the shift from extended families to nuclear families, the increasing participation of women in the labor market, the development of digital media, as well as socio-economic inequalities, have all contributed to reshaping leisure patterns within Algerian families. The results also show that family leisure has become a field of interaction between traditional values and modern patterns, between collective and digital leisure, and between economic capabilities and cultural choices. The article concludes that the recreational orientation of the Algerian family is the outcome of complex and evolving social dynamics, which calls for more comprehensive public policies to support family leisure and enhance its role in strengthening social bonds and improving quality of life.